(3ebUhQI GdechOis - (3CHhRjO YHO GdQMef Hf Ydj GdechOj GdaGSj,J (B807 (3g` s
(3ChdgG (B:s
(3CQbfi LGQa aLOG EP SQG jQbV eG Hjf ai COi hKfG s
(3BNQgG (B:s
(3hUd UdGI efgG JJQkG CHOkG Ydjg eG gHJ Ydi GdQhV GdUHG EfJgJ GdebUhQI dSjOi GdechOi QVi Gddg Yfg s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B1s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B3 - (3U (B318s
(3eUOQ GbJfGA GdCUd (B:s
(3GdQHGW (B(491(3c(B) s
Keywords: (3GdeLGejYs